Solar Photoelectro-Fenton treatment of pisco vinasse: a sustainable approach for organic load reduction and effluent valorization - Godoy-Perez, M (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This work evaluated the effectiveness of the Solar Photoelectro-Fenton (SPEF) process for treating vinasse from pisco production, an effluent with high organic load, acidic pH, and significant environmental impact. The study considered: i) comparison with photochemical (photolysis) and electrochemical (H2O2-assisted electro-oxidation and electro-Fenton) processes, ii) the effect of different current densities, and iii) the influence of UVA radiation. SPEF demonstrated the highest performance, achieving reductions of 70 % in COD, 47 % in TOC, and 53 % in polyphenols when applying 50 mA cm-2 for 360 min. This applied current condition presented the lowest values of energy consumption per unit mass of TOC and costs, compared to higher currents that accelerated mineralization but significantly increased energy consumption. Solar radiation was a determining factor on sunny days, maximum efficiencies and lowest costs were achieved, while on cloudy days, efficiency decreased significantly. Analysis of the post-SPEF effluent identified six carboxylic acids as degradation products, highlighting the persistence of oxalic, malonic, and tartaric acids, as well as an increase in the concentration of succinic, acetic, and formic acids, which explains the residual fraction of COD and TOC. Based on these results, the SPEF process is positioned as an efficient, sustainable, and low-cost alternative for vinasse treatment.